The Effect of Storytelling Method on Students’ Reading Comprehension: Pengaruh Metode Bercerita terhadap Pemahaman Membaca Siswa - Nurwahidah; Suratman; Muhammad Yani (ELOQUENCE : Journal of Foreign Language, 2026)
Background: Students at State Junior High School (SMPN) 4 Monta experience difficulties in reading comprehension, particularly in identifying main ideas, understanding supporting details, following sequences, and drawing conclusions. Limited vocabulary, low interest in reading, and passive participation may contribute to these difficulties. Purpose: This study examined the effectiveness of the storytelling method in improving students’ reading comprehension at State Junior High School (SMPN) 4 Monta. Method: This quantitative study employed a true experimental design with a pre-test and post-test control group design. The participants were 43 eighth-grade students, consisting of 23 students in the experimental group and 20 students in the control group. The experimental group received storytelling instruction using narrative texts, while the control group received conventional instruction. Data were collected through reading comprehension tests and analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene’s test of homogeneity, a baseline equivalence test, paired-samples t-tests, an independent-samples t-test, and Cohen’s d effect size. Results and Discussion: The experimental group’s mean score increased from 52.74 to 82.13, while the control group’s mean score increased from 49.95 to 63.40. The independent-samples t-test showed a statistically significant difference between the groups, t(41) = −7.406, p < 0.001, with an absolute mean difference of 18.730 points and a large effect size (d = 2.26). These findings indicate that storytelling produced greater improvement in reading comprehension than conventional instruction. The narrative structure and contextualized presentation of vocabulary may have supported students in organizing information, activating prior knowledge, and constructing meaning from narrative texts. Conclusions and Implications: The findings demonstrate that storytelling significantly improved students’ reading comprehension and produced greater gains than conventional instruction. Storytelling may therefore be considered an alternative instructional strategy for teaching narrative texts in EFL classrooms, particularly at the junior high school level. Future studies should involve larger and more diverse samples, longer treatment periods, different educational contexts, and various text types to further examine the effectiveness and applicability of storytelling in English language learning.